Comparison of drug advertisements published in Indian and foreign journals - Sharma, Ashok Kumar; Dahiya, Navdeep; Chuki, Pem (International Journal of Research in Medical Sciences, 2017)
Background: Drug advertisements form one of the major sources for updating drug information by the medical professionals. It has been observed that Indian drug advertisements provide incomplete and poor quality of essential information. However, existing information on comparison of drug advertisements in Indian and foreign journals is limited. Hence, this study was planned to compare the drug advertisements published in Indian and foreign journals. Methods: A total of 200 drug advertisements, 100 each from Indian and foreign journals, were randomly selected excluding those of medical devices, surgical appliances, nutritional supplements and ayurvedic drugs. The drug advertisements from two sources were compared for drug groups, compliance to ‘Ethical criteria for medicinal drug promotion’ of World Health Organization (WHO), retrievability of cited reference(s) and mention of any additional information. Results: Drug groups advertised frequently in the Indian journals were those used for chronic diseases whereas chemotherapeutic agents topped the list in foreign journals. Brand names were mentioned in 100% advertisements in both categories of journals whereas information on other ingredients known to cause problems was not mentioned in any of the studied advertisements. Overall, compliance to WHO guidelines by advertisements was 54.6% in Indian journals and 68.2% in foreign journals. The two categories of journals didn’t differ significantly in retrievability of cited reference(s) and additional information except for information on drug storage which was significantly more mentioned in Indian journals. Conclusions: Drug advertisements in both Indian and foreign journals were incomplete for updating drug information by medical professionals.